KEPEMIMPINAN DALAM ISLAM: KAJIAN TEMATIK DALAM AL-QURAN DAN HADITS - Umar Sidiq (Dialogia, 2014)
AbstractThe most basic ethics in leadership is responsibility. Humans living in this world is called the leader. Therefore, as a leader, humans hold responsibility, at least to themselves. A husband and a wife are responsible for their children, an employer is to the workers, and a top leader is to his subordinates. A president, a governor, and a regent are accountable to the people they lead. Etika yang paling pokok dalam kepemimpinan adalah tanggung jawab. Manusia yang hidup di dunia ini disebut pemimpin. Oleh karena itu, sebagai pemimpin manusia memegang tanggungjawab, sekurang-kurangnya terhadap dirinya sendiri. Seorang suami bertanggung jawab kepada isteri dan anak-anaknya. Seorang majikan bertanggung jawab kepada pekerjanya. Seorang pimpinan bertanggungjawab kepada bawahannya. Seorang presiden, gubernur, dan bupati bertanggung jawab kepada rakyat yang dipimpinnya. Keywords: kepemimpinan, Islam, dan al-Quran Hadits